A method of forming an alumina support
Alumina supports with high strength and high porosity were prepared by mixing aluminum-containing compound A with regular morphology B and treating with a pectin, which solved the problem of insufficient strength and porosity in the prior art and improved the performance of alumina supports in industrial applications.
Patent Information
- Application Number
- CN202410218862.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-02-28
AI Technical Summary
Existing technologies make it difficult to prepare alumina supports that combine high mechanical strength, high specific surface area, and high porosity, which affects their performance in industrial applications.
Alumina carriers were prepared by mixing aluminum compound A with aluminum compound B with regular morphology, adding a binder and a peptide, and kneading, molding, drying and calcining. The porous skeleton was formed by the overlap of the regularly morphological powders and the action of the binder, which improved the mechanical strength and porosity.
The prepared alumina support has higher mechanical strength and porosity, meeting the mechanical performance requirements of industrial applications, while maintaining good mass transfer characteristics.
Smart Images

Figure CN118217960B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of industrial catalysis technology and relates to a method for forming an alumina support, specifically a method for forming an alumina support with high strength, high specific surface area and high porosity. Background Technology
[0002] Solid catalysts or supports are mostly powder materials before molding. The molding process of powders is closely related to their basic physical properties, such as particle shape, particle size, density, and pore structure. Among these, particle shape not only significantly affects the powder's flowability, mixability, filling characteristics, and ability to interact with fluids, but also directly influences the powder's behavior in the operating unit. For example, particle shape is one of the important factors to consider in the design and operation of units such as powder storage and transportation, mixing and separation, crystallization and sintering, and fluidization.
[0003] Common shapes of powder particles include spherical, columnar, plate-like, polyhedral, and irregular shapes. When powders of different shapes are mixed and packed together, they exhibit differences in porosity and the number of contact points (coordination number). Generally, porosity increases as sphericity decreases. In loose packing, angular particles have higher porosity and lower coordination number. Particles with higher surface roughness also have greater packing porosity. Furthermore, using powders of different sizes for particle gradation can also allow for directional control of the packing pore structure.
[0004] Industrial alumina supports, under operating conditions, must withstand the impact and abrasion caused by transportation, loading, thermal expansion, and fluid flow on the particles, while also ensuring low-resistance diffusion of fluids within the pores. This requires alumina supports to possess not only high mechanical strength but also excellent mass transfer properties. During powder forming, rational design and control of particle size distribution and the introduction of regular morphology can optimize the microstructure, potentially yielding alumina supports with high strength and high porosity.
[0005] In conclusion, developing alumina carriers that combine high mechanical strength, high specific surface area, and high porosity is of great significance. Summary of the Invention
[0006] In view of the above-mentioned existing technical situation, the present invention proposes a method for forming an alumina carrier. The main contents are as follows:
[0007] A method for forming an alumina carrier includes the following steps:
[0008] (1) Mix aluminum-containing compound A and aluminum-containing compound B evenly to obtain a mixed powder;
[0009] (2) Add water, adhesive, and binder to the mixed powder, and then knead it;
[0010] (3) The material obtained in step (2) is shaped, dried and calcined to obtain an alumina carrier;
[0011] The aluminum-containing compound A is an alumina precursor, which is one or more of boehmite, pseudoboehmite, gibbsite, and ammonium aluminum carbonate; the aluminum-containing compound B is alumina or its precursor with a regular morphology, which is rod-shaped, plate-shaped, flower-shaped, fibrous, polyhedral, or needle-shaped, and the aspect ratio of the regular morphology is 3-20.
[0012] The mesoscopic morphology of the aluminum-containing compound A is rod-shaped, plate-shaped, flower-shaped, fibrous, polyhedral, needle-shaped, spherical, or irregular in shape.
[0013] The median diameter of the aluminum-containing compound B is 1.4-2.8 times that of the aluminum-containing compound A.
[0014] The mass ratio of aluminum-containing compound A to aluminum-containing compound B is 0.2-7.
[0015] The amount of water used is 0.6-1.0 times the mass of the mixed powder.
[0016] The adhesive solvent is one or more of acetic acid, oxalic acid and nitric acid, and its amount is 1-6.5% of the mass of the mixed powder.
[0017] The binder is one or more of methylcellulose, hydroxypropyl methylcellulose, microcrystalline cellulose, guar gum powder, starch, polyvinyl alcohol, and polyvinylpyrrolidone, and its amount is 0.2%-10% of the mixed powder by mass.
[0018] The adhesive is fed separately or mixed evenly with water and adhesive solvent before being fed together.
[0019] The equipment used for molding is a combination of various types of equipment, including kneaders, twin-screw extruders, single-screw extruders, pelletizers, sugar coating machines, and shot blasting machines.
[0020] The drying process involves first drying at 20-30℃ for 10-24 hours, then drying with forced air at 20-30℃ for 2-8 hours, and finally raising the temperature to 40-80℃ and drying with forced air for 2-6 hours.
[0021] The calcination temperature is 300-1100℃, the calcination time is 2-6h, and the heating rate is 1-10℃ / min.
[0022] The resulting alumina carrier can be spherical, cylindrical, or clover-shaped.
[0023] The alumina carrier has the following properties: specific surface area of 150-350 m². 2 / g, diameter shrinkage rate 7-16%, compressive strength 120-200N / cm or 30-100N / particle.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] In the preparation of alumina supports, alumina precursors are compounded with alumina or its precursors having regular morphologies. Regularly shaped powder particles overlap and stack to form a porous framework, while the dissolved alumina precursors, with their higher fluidity, can fill the gaps between particles and form liquid bridges at the interface, thus improving adhesion. On the other hand, the dissolved alumina precursors can reduce inter-particle friction and extrusion pressure, preserving the integrity of the alumina morphology to some extent, which is beneficial for improving the porosity of the framework. After heat treatment, the alumina precursors decompose into alumina and undergo volume shrinkage, adhering to the surface of the regularly shaped powder particles or forming new alumina solid bridges at the interface, ultimately improving the porosity, mechanical strength, and specific surface area of the support. Furthermore, the particle size difference between aluminum compounds A and B can further promote the dispersion of fine particles in the gaps or interfaces of coarse particles, increasing the contact area between particles, promoting the aforementioned dissolution process and the formation of liquid-solid bridges, thereby further improving the mechanical properties of the molded sample. Attached Figure Description
[0026] Figure 1 This is a scanning electron microscope (SEM) image of the pseudoboehmite powder in Example 1.
[0027] Figure 2 This is a scanning electron microscope (SEM) image of the alumina powder with a regular morphology in Example 1.
[0028] Figure 3 This is a scanning electron microscope (SEM) image of the axial cross-section of the alumina carrier in Example 2.
[0029] Figure 4 This is a scanning electron microscope (SEM) image of the axial section of the alumina support in Comparative Example 1.
[0030] Figure 5 This is a scanning electron microscope (SEM) image of the axial section of the alumina support in Comparative Example 2. Detailed Implementation
[0031] In this invention, the synthesis method of rod-shaped alumina and sheet-shaped alumina is described in patent ZL201710944136.1.
[0032] In this invention, the water-to-powder ratio is the mass ratio of water to powder. The acid-to-powder ratio is the mass ratio of the binder to the powder.
[0033] In this invention, the mechanical strength / compressive strength can refer to the radial compressive strength of the cylindrical alumina carrier or the point compressive strength of the spherical alumina carrier. The average compressive strength is the arithmetic mean calculated after sampling and testing.
[0034] In this invention, the water absorption rate of the alumina carrier refers to the ratio of the weight change of the dried alumina carrier before and after soaking in excess deionized water for 60 minutes to the weight of the dried alumina carrier. The specific test method is as follows: The alumina carrier to be tested is dried in an oven at 120℃ for 4 hours. 2-3g of the dried alumina carrier is weighed as the test sample, and its weight is recorded as m1. The sample is soaked in an appropriate amount of deionized water for 60 minutes. Then, the solid phase is filtered, and excess water on the sample surface is removed with filter paper. The weight of the solid sample is quickly weighed and recorded as m2. The water absorption rate of the carrier is calculated using the following formula: Water absorption rate = ((m2-m1) / m1)*100%.
[0035] In this invention, the diameter shrinkage rate of the alumina carrier refers to the rate of change of the diameter of the calcined cylindrical alumina carrier compared to the diameter of the wet material when it is freshly extruded. The specific testing method is as follows: a certain amount of calcined cylindrical alumina carrier is taken, its diameter is measured using vernier calipers, and the average value is calculated and denoted as R2. The diameter of the freshly extruded alumina wet strip from the corresponding batch can be approximated as the aperture of the extrusion plate, denoted as R1. The diameter shrinkage rate of the carrier is calculated using the following formula: Diameter shrinkage rate = ((R2-R1) / R1)*100%.
[0036] The present invention will be further explained below through specific embodiments, but the following embodiments do not limit the present invention.
[0037] Example 1
[0038] Irregularly shaped pseudoboehmite (median diameter 6.8 μm, SEM image as shown) were weighed at a mass ratio of 5:1. Figure 1 (as shown) and rod-shaped alumina powder (median diameter 18 μm, aspect ratio 10-20, SEM image as shown) and rod-shaped alumina powder (median diameter 18 μm, aspect ratio 10-20, SEM image shown). Figure 2 30.0g of the mixture (as shown) was mixed evenly to obtain a mixed powder. Then, 0.6g of hydroxypropyl methylcellulose was added and stirred evenly to obtain a final mixture. A mixed solution of water and nitric acid was added to the mixture according to a water-to-powder ratio (mass ratio of water to mixed powder) of 0.7 and an acid-to-powder ratio (mass ratio of acid to mixed powder) of 0.05. The mixture was then kneaded 2-3 times using a twin-screw extruder without a perforated plate. A 2.0mm diameter perforated plate was then installed on the extruder to extrude the kneaded material, resulting in an extruded wet material. The wet material was dried overnight at room temperature, then dried in an oven at 25℃ for 6 hours, followed by drying at 50℃ for 2 hours. Finally, it was calcined at 600℃ to obtain a cylindrical alumina carrier, denoted as C1.
[0039] Example 2
[0040] The alumina support was prepared using the same method as in Example 1, except that the mass ratio of irregularly shaped boehmite to rod-shaped alumina powder was 3:1, denoted as C2.
[0041] Example 3
[0042] Weigh out 30.0g of irregularly shaped boehmite (median diameter 6.8μm) and rod-shaped alumina (median diameter 18μm, aspect ratio 10-20) at a mass ratio of 1:1, mix thoroughly to obtain a mixed powder, then add 0.6g of methylcellulose and stir until homogeneous to obtain a mixture. Add 22.5g of a 6.8wt% dilute nitric acid solution to the mixture dropwise and stir until homogeneous. Knead the mixture 2-3 times using a twin-screw extruder without a perforated plate. Then extrude the kneaded material using a 2.0mm diameter perforated plate to obtain an extruded wet material. Dry the wet material overnight at room temperature, then in an oven at 25℃ for 6 hours, then at 50℃ for 2 hours, and finally calcine at 600℃ to obtain a cylindrical alumina carrier, denoted as C3.
[0043] Example 4
[0044] Weigh out 30.0g of irregularly shaped boehmite (median diameter 6.8μm) and flake-shaped alumina (median diameter 15, aspect ratio 3-12) at a mass ratio of 7:1, mix them evenly to obtain a mixed powder, then add 1.5g of guar gum powder and stir evenly to obtain a mixture. Add a water-acetic acid solution to the above mixture at a water-to-powder ratio of 0.6 and an acid-to-powder ratio of 0.08, and knead the mixture 2-3 times using a twin-screw extruder without a perforated plate. Then, install a 2.0mm diameter perforated plate on the extruder to extrude the kneaded material to obtain an extruded wet material. Dry the wet material overnight at room temperature, then dry it in an oven at 25-30℃ for 4-8 hours, then dry it at 50℃ for 2-4 hours, and finally calcine it at 500℃ to obtain a cylindrical alumina carrier, denoted as C4.
[0045] Example 5
[0046] 3000g of irregularly shaped boehmite (median diameter 6.8μm) and rod-shaped alumina powder (shape and specifications same as in Example 1) were weighed out at a mass ratio of 1:1 and loaded into a kneader. Water and nitric acid were premixed at a water-to-powder ratio of 0.65 and an acid-to-powder ratio of 0.03. Then, 45g of methylcellulose was added to the mixture to prepare an additive mixture. The mixture was poured into the kneader and kneaded for 20-50 minutes. The resulting alumina wet pellets were then obtained through extrusion, pelletizing, and shot blasting. The wet pellets were dried overnight at room temperature, then gradually heated and dried further, and finally calcined at 800℃ to obtain spherical alumina carriers with a diameter of approximately 2mm, denoted as S1.
[0047] Comparative Example 1
[0048] The molded article was prepared using the same method as in Example 1, except that a single irregular particle of boehmite powder, denoted as C5, was used as the powder raw material.
[0049] Comparative Example 2
[0050] The molded article was prepared using the same method as in Example 1, except that a single rod-shaped alumina powder, denoted as C6, was used as the powder raw material.
[0051] Comparative Example 3
[0052] The molded article was prepared using the same method as in Example 1, except that the powder raw material used was a mixture of pseudoboehmite and alumina powder obtained by calcining pseudoboehmite at 600°C, denoted as C7.
[0053] The characterization data of the obtained samples are shown in Table 1:
[0054] Table 1 Sample Parameters
[0055]
[0056]
[0057] As can be seen from the data in Table 1, mixing alumina precursors with alumina of different morphologies can achieve higher strength and water absorption than using either powder alone. For example... Figure 4 As shown, when using irregularly shaped pseudoboehmite alone, a relatively dense packing structure can be obtained, which may result in a lower porosity. This also corresponds to the lower water absorption rate and higher diameter shrinkage rate of C5 in Table 1. Figure 5 The image shows a cross-section of a sample formed using rod-shaped alumina alone. It reveals that under extrusion pressure, the rod-shaped structure breaks into small segments that overlap, forming a rich porous network, corresponding to the high water absorption and low diameter shrinkage of C6. However, the low colloidal solubility of alumina and the limited contact area of the rod-shaped structure result in low mechanical strength of the formed sample, failing to meet industrial requirements. When the alumina precursor is compounded with regularly shaped alumina powder in a certain proportion, the rod-shaped structures with a larger aspect ratio accumulate to form a porous framework, increasing porosity. Simultaneously, the colloidal boehmite fills the gaps between the rod-shaped structures and forms liquid bridges at the particle interfaces, acting as a binder. The colloidal alumina precursor reduces inter-particle friction and lowers extrusion pressure, preserving the integrity of the alumina morphology to some extent, which is beneficial for improving the packing porosity of the framework. After heat treatment of the wet material, the boehmite decomposes to form new Al-O-Al bonds, forming stable solid bridges between particles (such as...). Figure 3(As shown), this improves the mechanical strength of the composite molded article. The method of this invention balances the porosity and mechanical strength of the alumina carrier, does not introduce impurities, and is simple and easy to implement.
[0058] The above description is only a few embodiments of the present invention and is not intended to limit the present invention. Any modifications, substitutions and alterations made in accordance with the claims of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for forming an alumina carrier, characterized in that: Includes the following steps: S1. Mix aluminum-containing compound A and aluminum-containing compound B evenly to obtain a mixed powder; S2 Add water, adhesive solvent, and binder to the mixed powder, and then knead it; S3 The material obtained in step S2 is shaped, dried and calcined to obtain an alumina carrier; The aluminum-containing compound A is an alumina precursor, which is one or more of boehmite, pseudoboehmite, gibbsite, and ammonium aluminum carbonate; the aluminum-containing compound B is alumina with a regular morphology, which is rod-shaped, plate-shaped, fibrous, polyhedral, or needle-shaped, and the aspect ratio of the regular morphology is 3-20; the median diameter of the aluminum-containing compound B is 1.4-2.8 times that of the aluminum-containing compound A; the powder particles of the aluminum-containing compound B with a regular morphology overlap and stack to form a porous framework, and the dissolved aluminum-containing compound A fills the gaps between the particles and forms liquid bridges at the interface to improve the adhesion. After calcination, the alumina precursor decomposes into alumina and undergoes volume shrinkage, adhering to the surface of the powder particles with a regular morphology, or forming new alumina solid bridges at the interface.
2. The method for forming an alumina carrier as described in claim 1, characterized in that: The mass ratio of aluminum-containing compound A to aluminum-containing compound B is 0.2-7.
3. The method for forming an alumina carrier as described in claim 1, characterized in that: The amount of water used is 0.6-1.0 times the mass of the mixed powder.
4. The method for forming an alumina carrier as described in claim 1, characterized in that: The adhesive solvent is one or more of acetic acid, oxalic acid and nitric acid, and its amount is 1-6.5% of the mass of the mixed powder.
5. The method for forming an alumina carrier as described in claim 1, characterized in that: The binder is one or more of methylcellulose, hydroxypropyl methylcellulose, microcrystalline cellulose, guar gum powder, starch, polyvinyl alcohol and polyvinylpyrrolidone, and its amount is 0.2%-10% of the mixed powder by mass.
6. The method for forming an alumina carrier as described in claim 1, characterized in that: The drying process involves first allowing the product to stand at 20-30°C for 10-24 hours, then drying it with forced air at 20-30°C for 10-24 hours, and finally raising the temperature to 40-80°C and drying it with forced air for 2-8 hours.
7. The method for forming an alumina carrier as described in claim 1, characterized in that: The roasting temperature is 300-1100 ℃, and the roasting time is 2-6 h.
Citation Information
Patent Citations
Method for preparing nano-alumina carrier with defect-rich surface
CN107824172A
Double pore distribution alumina carrier and preparation method thereof, and hydrodemetallization catalyst
CN109718747A
Macroporous alumina carrier and preparation method thereof
CN116037085A
